High-temperature wear-resistant nickel-based metal-ceramic composite coating and preparation method thereof

By introducing Al2O3 ceramics and h-BN or Ag and Mo powders into the nickel-based coating, the nickel-based metal-ceramic composite coating was prepared by explosive spraying technology, which solved the problem of poor friction and wear performance of nickel-based coating at high temperatures. It achieves low wear rate and high hardness at high temperatures, and is suitable for high-speed and high-temperature working conditions.

CN119121108AInactive Publication Date: 2024-12-13LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202411278079.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing nickel-based coating has poor friction and wear performance at high temperatures and has low bond strength, making it difficult to meet the needs of mechanical components under high speed, high temperature and heavy load conditions.

Method used

70% NiCrAlY powder is used as the matrix, 10~20% Al2O3 ceramic powder is used as the wear-resistant phase, and 10~20% lubricated phase is composed of h-BN or Ag and Mo powder. High-temperature wear-resistant nickel is prepared by explosive spraying technology. Base metal-ceramic composite coating to improve the hardness and bond strength of the coating.

Benefits of technology

The hardness and bonding strength of the coating are significantly improved, and the wear rate at high temperature of 900°C is reduced to 10-6mm3/N·m. The coating has good wear resistance and lubrication performance in the range of room temperature to 900°C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121108A_ABST
    Figure CN119121108A_ABST
Patent Text Reader

Abstract

The invention relates to a high-temperature wear-resistant nickel-based metal-ceramic composite coating, which consists of the following components in percentage by mass: 70 percent of NiCrAlY powder serving as a matrix, 10 to 20 percent of Al2O3 ceramic powder serving as a wear-resistant phase and 10 to 20 percent of a lubricating phase, the lubricating phase is composed of one or two of h-BN, Ag powder and Mo powder; the h-BN is nickel-coated core-shell structure powder with the mass fraction of 60% of metal Ni serving as a shell layer and coated on the periphery of 40% of an h-BN core. Meanwhile, the invention further discloses a preparation method of the composite coating. The composite coating has good compactness and high hardness and bonding strength, and the wear rate at the high temperature of 900 DEG C can be reduced to 10 <-6 > mm < 3 > / N.m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials and advanced coatings, and in particular to a high-temperature wear-resistant nickel-based metal-ceramic composite coating and a preparation method thereof. Background Art

[0002] Friction and wear are one of the main causes of failure of mechanical moving parts. With the rapid development of technology fields such as aviation, aerospace, and nuclear industry, higher requirements are placed on the lubrication and wear resistance of mechanical parts under harsh working conditions such as high speed, high temperature, and heavy load. Using advanced surface technology to prepare coating materials with lubrication and wear resistance on the surface of metal mechanical parts is an important way to improve the tribological properties of mechanical moving parts and increase the reliability and life of high-temperature operation.

[0003] As an advanced surface coating preparation technology, explosion spraying is a method of mixing oxygen and fuel gas in a certain proportion and then detonating it. The energy generated by the pulsed gas combustion explosion is used to heat the spray powder to a molten or semi-molten state and accelerate it to impact the substrate surface to form a coating with a certain thickness. It has a wide spraying range and is suitable for the preparation of coating materials such as metals, alloys, and ceramics. The coating has the characteristics of low porosity and high bonding strength. In addition, the explosion spraying method has a lower temperature than traditional thermal spraying methods such as flame spraying and plasma spraying, and causes less thermal damage to the substrate.

[0004] Nickel-based alloys are widely used in various engineering fields, such as industrial gas turbines, aircraft and automobile engines, and internal combustion engines, due to their advantages of high strength, low density, strong corrosion resistance, and good wettability and adhesion. However, the hardness of nickel-based coatings is relatively low. Under friction and wear conditions, especially when working at high temperatures, the wear resistance of the coatings is poor and the service life is short. At present, adding solid lubricants and wear-resistant phases to nickel-based alloys to obtain composite coatings that can achieve friction reduction and wear resistance at high temperatures is the preferred solution to solve the friction and wear problems of nickel-based coatings at high temperatures.

[0005] There are patent literature reports on nickel-based coatings and their preparation methods. Patent CN 109868443 B discloses a nickel-based alumina high-temperature self-lubricating wear-resistant coating and its preparation method. The NiCoCrAlY / Al2O3-CaF2.BaF2 high-temperature lubricating wear-resistant coating is prepared by supersonic flame spraying technology. Since CaF2.BaF2 only softens under high temperature conditions and forms a lubricating film on the coating surface under shear stress, the coating only obtains a low friction coefficient at a high temperature of 800°C, while the friction coefficient in the medium and low temperature range (room temperature ~ 400°C) is still high, and the wear rate is high (10 -4 mm 3 / N·m order of magnitude), and the mechanical properties of the coating are not considered. Patent CN 115537704 B discloses a method for preparing a nickel-based lubricating coating by explosion spraying. The prepared NiCrAlY-Ag lubricating coating has excellent lubrication performance in the low temperature range (room temperature ~ 300 ℃), and the layer-base bonding strength is 40 MPa. Patent CN116445846A discloses a nickel-based self-lubricating coating with a wide temperature range. The NiCrAlYTa-Ag composite coating prepared by explosion spraying technology has a friction coefficient of 0.36~0.55 in the range of room temperature to 900 ℃, and the wear rate at 900 ℃ is (5.58~9.02)×10 -5 mm 3 / N·m, and the bonding strength is 43~50 MPa. It can be seen that the bonding strength of the above nickel-based coating is still low, and because only soft metal Ag is introduced as the lubricating phase, the hardness of the coating is low and the wear resistance still needs to be improved. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a high-temperature wear-resistant nickel-based metal-ceramic composite coating with good comprehensive properties (mechanical properties and tribological properties).

[0007] Another technical problem to be solved by the present invention is to provide a method for preparing the high-temperature wear-resistant nickel-based metal-ceramic composite coating.

[0008] To solve the above problems, the present invention discloses a high-temperature, wear-resistant nickel-based metal-ceramic composite coating, characterized in that: the coating is composed, by mass percentage, of 70% NiCrAlY powder as a matrix, 10-20% Al2O3 ceramic powder as a wear-resistant phase and 10-20% lubricating phase; the lubricating phase is composed of one or two of h-BN, Ag powder and Mo powder; the h-BN refers to a nickel-coated core-shell structure powder in which a 40% h-BN core is coated with a shell layer containing 60% metal Ni by mass.

[0009] When the lubricating phase is h-BN, the mass fraction of h-BN is 10% or 20%.

[0010] When the lubricating phase consists of Ag powder and Mo powder, the mass ratio of the Ag powder to the Mo powder is 2:1.

[0011] The particle size of the NiCrAlY powder is 15-45 μm; the particle size of the Al2O3 ceramic powder is 15-40 μm; the particle size of the h-BN is 5-100 μm; the particle size of the Ag powder is 15-55 μm; and the particle size of the Mo powder is 20-55 μm.

[0012] The Vickers hardness of the coating is 582~678 Hv0.2 The bonding strength is greater than 60 MPa, and the wear rate at 900 °C is reduced to 10 -6 mm 3 / N·m.

[0013] The method for preparing the high temperature wear-resistant nickel-based metal-ceramic composite coating as described above comprises the following steps: ⑴Preparation of spray powder: Weigh NiCrAlY powder, Al2O3 ceramic powder and lubricating phase powder according to a proportion, and mix the NiCrAlY powder, Al2O3 ceramic powder and lubricating phase powder uniformly by mechanical mixing to obtain spraying powder; ⑵Substrate pretreatment: The surface of the 304 stainless steel substrate was first ultrasonically cleaned with anhydrous ethanol for 0.5 h, then sandblasted, then ultrasonically cleaned with anhydrous ethanol for 0.5 h, and finally dried to obtain a pretreated substrate. ⑶Preparation of coating: First, a NiCrAlY bonding layer with a thickness of 30-50 μm is deposited on the surface of the pretreated substrate by using the explosion spraying technology, and then the spraying powder is deposited on the NiCrAlY bonding layer by using the explosion spraying technology. After cooling to room temperature, a high-temperature wear-resistant nickel-based metal-ceramic composite coating is obtained.

[0014] The mechanical mixing conditions in step (1) are to use a planetary ball mill, the grinding balls are steel balls, the ball-to-material ratio is 1:1-1:2, the rotation speed is 250-300 r / min, and the mixing time is 5-8 h.

[0015] The sandblasting conditions in step (2) refer to using corundum sand with a particle size of 100-200 μm, a sandblasting pressure of 0.5-0.8 MPa, a sandblasting angle of 40-90°, and a sandblasting distance of 50-100 mm.

[0016] The conditions for explosion spraying in step (3) refer to using a mixed gas of oxygen and fuel gas with an oxygen-fuel ratio of 1.1:1~1.3:1, the fuel gas is a mixture of acetylene and propane, the inflation volume is 45%~50%, the spraying frequency is 3~5 Hz, the spraying distance is 150~200 mm, and nitrogen is used as the powder delivery carrier gas and protective gas.

[0017] Compared with the prior art, the present invention has the following advantages: 1. The present invention introduces Al2O3 ceramic wear-resistant phase and lubricating phase (h-BN or Ag and Mo powder) to improve the mechanical properties and wear resistance of the prepared metal-ceramic composite coating while having lubricating properties, thereby improving the comprehensive performance of the nickel-based coating, and further making the coating have important application prospects in mechanical parts moving under harsh working conditions such as high speed, high temperature, and heavy load.

[0018] 2. The metal-ceramic composite coating prepared by the present invention has good compactness, high hardness and bonding strength. The Vickers hardness reaches 582~678 Hv 0.2 The hardness of the NiCrAlY matrix is ​​significantly improved; the maximum bonding strength reaches 76 MPa, which is significantly better than the bonding strength of the coating prepared by atmospheric plasma spraying technology.

[0019] 3. The solid lubricant h-BN or solid lubricants Ag and Mo in the present invention can give the NiCrAlY-based composite coating good lubrication performance in different temperature ranges. The addition of hard ceramic phase Al2O3 makes the coating have good wear resistance in a wide temperature range from room temperature to 900 ℃, especially at a high temperature of 900 ℃, the wear rate can be reduced to 10 -6 mm 3 / N·m.

[0020] 4. The explosion spraying technology adopted in the present invention can realize the preparation of metal and ceramic composite coating materials, and has little damage to the substrate, low degree of oxidation of the coating, controllable process and high preparation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0022] Figure 1 This is a cross-sectional microstructure diagram of the composite coating prepared in Example 1 of the present invention.

[0023] Figure 2 The wear rate diagram of the composite coating and the pure NiCrAlY metal coating prepared in Examples 1 and 2 of the present invention.

[0024] Figure 3 This is a cross-sectional hardness diagram of the composite coating prepared in Examples 3 to 5 of the present invention. DETAILED DESCRIPTION

[0025] A high-temperature wear-resistant nickel-based metal-ceramic composite coating, which, by mass percentage (g), consists of 70% NiCrAlY powder as a matrix, 10-20% Al2O3 ceramic powder as a wear-resistant phase and 10-20% lubricating phase; the lubricating phase consists of one or two of h-BN, Ag powder and Mo powder; h-BN refers to a nickel-coated core-shell structure powder in which 60% by mass of metal Ni is used as a shell layer and a 40% by mass of h-BN core is coated.

[0026] The Vickers hardness of the coating is 582~678 Hv 0.2 The bonding strength is greater than 60 MPa, and the wear rate at 900 °C is reduced to 10 -6 mm 3 / N·m.

[0027] Wherein: when the lubricating phase is h-BN, the mass fraction of h-BN is 10% or 20%.

[0028] When the lubricating phase consists of Ag powder and Mo powder, the mass ratio (g / g) of Ag powder to Mo powder is 2:1.

[0029] The particle size of NiCrAlY powder is 15~45 μm; the particle size of Al2O3 ceramic powder is 15~40 μm; the particle size of h-BN is 5~100 μm; the particle size of Ag powder is 15~55 μm; and the particle size of Mo powder is 20~55 μm.

[0030] A method for preparing a high-temperature wear-resistant nickel-based metal-ceramic composite coating comprises the following steps: ⑴Preparation of spray powder: Weigh NiCrAlY powder, Al2O3 ceramic powder and lubricating phase powder according to the proportion, and use a planetary ball mill to mechanically mix NiCrAlY powder, Al2O3 ceramic powder and lubricating phase powder, with steel balls, a ball-to-material ratio (g / g) of 1:1-1:2, a rotation speed of 250-300 r / min, and a mixing time of 5-8 h. Mix evenly to obtain spray powder.

[0031] ⑵Substrate pretreatment: The surface of the 304 stainless steel substrate (Φ25.4 mm×8 mm) was first ultrasonically cleaned with anhydrous ethanol for 0.5 h to remove surface oil stains, and then sandblasted with corundum sand with a particle size of 100-200 μm, with a sandblasting pressure of 0.5-0.8 MPa, a sandblasting angle of 40-90°, and a sandblasting distance of 50-100 mm. Anhydrous ethanol was then ultrasonically cleaned for 0.5 h to remove residual grit on the surface, and finally dried to obtain the pretreated substrate.

[0032] ⑶Preparation of coating: First, a NiCrAlY bonding layer with a thickness of 30-50 μm is deposited on the surface of the pretreated substrate by explosion spraying technology, and then the spray powder is deposited on the NiCrAlY bonding layer by explosion spraying technology. After cooling to room temperature, a high-temperature wear-resistant nickel-based metal-ceramic composite coating is obtained.

[0033] Among them: the conditions for explosion spraying refer to the use of a mixed gas of oxygen and fuel gas with an oxygen-fuel ratio of 1.1:1~1.3:1, the fuel gas is a mixture of acetylene and propane, the gas volume is 45%~50%, the spraying frequency is 3~5 Hz, the spraying distance is 150~200mm, and nitrogen is used as the powder carrier gas and protective gas.

[0034] Example 1 A method for preparing a high-temperature wear-resistant nickel-based metal-ceramic composite coating comprises the following steps: ⑴Preparation of spray powder: 105 g of NiCrAlY powder, 30 g of Al2O3 ceramic powder and 15 g of h-BN@Ni powder (NiCrAlY, Al2O3 and h-BN@Ni accounted for 70%, 20% and 10% by mass respectively) were mechanically mixed in a planetary ball mill, with steel balls, a ball-to-material ratio of 1:2, a rotation speed of 300 r / min and a mixing time of 6 h. After uniform mixing, NiCrAlY / 20Al2O3 / 10h-BN mixed powder was obtained.

[0035] ⑵Substrate pretreatment: The 304 stainless steel substrate was sandblasted with corundum sand with a particle size of 100-200 μm, the sandblasting pressure was 0.6-0.7 MPa, the sandblasting angle was 50-60°, and the sandblasting distance was 60-70 mm. The stainless steel substrate was ultrasonically cleaned in anhydrous ethanol for 0.5 h before and after sandblasting. Finally, it was blown dry to obtain the pretreated substrate.

[0036] ⑶Preparation of coating: First, a NiCrAlY bonding layer with a thickness of about 40 μm was deposited on the surface of the pretreated substrate by explosion spraying technology, with an oxygen-fuel ratio of 1.1:1, an aeration volume of 45%-50%, a spraying frequency of 3 Hz, and a spraying distance of 150 mm. Then, NiCrAlY / 20Al2O3 / 10h-BN mixed powder was deposited on the NiCrAlY bonding layer by explosion spraying technology, with an oxygen-fuel ratio of 1.3:1, an aeration volume of 45%-50%, a spraying frequency of 4 Hz, and a spraying distance of 200 mm. After cooling to room temperature, the NiCrAlY / 20Al2O3 / 10h-BN composite coating was obtained.

[0037] The cross-sectional microstructure of the obtained coating is shown in Figure 1 As shown. Figure 1 It can be seen that the composite coating has a typical layered structure.

[0038] The mechanical properties of the obtained coating were tested: the Vickers hardness was 678 Hv 0.2 , the bonding strength is 76 MPa.

[0039] The tribological properties of the coating from room temperature to 900 ℃ were tested in an atmospheric environment using a high-temperature reciprocating friction and wear tester. A Si3N4 ceramic ball with a diameter of 6 mm was selected as the friction pair, with a load of 5 N, a reciprocating speed of 0.05 m / s, a reciprocating length of 5 mm, and a running time of 30 min. The friction coefficient and wear rate are shown in Table 1. The friction coefficient of the NiCrAlY / 20Al2O3 / 10h-BN composite coating at 900 ℃ is 0.48, and the wear rate from room temperature to 600 ℃ is 10 -5 mm 3 / N·m, and the wear rate at 900 ℃ is as low as 6.3×10 -6 mm 3 / N·m.

[0040] Table 1 Tribological properties test results Example 2 A method for preparing a high-temperature wear-resistant nickel-based metal-ceramic composite coating comprises the following steps: ⑴Preparation of spray powder: 105 g of NiCrAlY powder, 15 g of Al2O3 ceramic powder and 30 g of h-BN@Ni powder (NiCrAlY, Al2O3 and h-BN@Ni mass percentages are 70%, 10% and 20%, respectively) were mechanically mixed in a planetary ball mill, with steel balls, a ball-to-material ratio of 1:2, a rotation speed of 250 r / min and a mixing time of 8 h. After uniform mixing, NiCrAlY / 10Al2O3 / 20h-BN mixed powder was obtained.

[0041] ⑵Substrate pretreatment: The 304 stainless steel substrate was sandblasted with corundum sand with a particle size of 100-200 μm, the sandblasting pressure was 0.7-0.8 MPa, the sandblasting angle was 60-70°, and the sandblasting distance was 70-80 mm. The stainless steel substrate was ultrasonically cleaned in anhydrous ethanol for 0.5 h before and after sandblasting. Finally, it was blown dry to obtain the pretreated substrate.

[0042] ⑶Preparation of coating: First, a NiCrAlY bonding layer with a thickness of about 40 μm was deposited on the surface of the pretreated substrate by explosion spraying technology, with an oxygen-fuel ratio of 1.1:1, an aeration volume of 45%-50%, a spraying frequency of 3 Hz, and a spraying distance of 150 mm. Then, NiCrAlY / 10Al2O3 / 20h-BN mixed powder was deposited on the NiCrAlY bonding layer by explosion spraying technology, with an oxygen-fuel ratio of 1.3:1, an aeration volume of 45%-50%, a spraying frequency of 5 Hz, and a spraying distance of 250 mm. After cooling to room temperature, the NiCrAlY / 10Al2O3 / 20h-BN composite coating was obtained.

[0043] The mechanical properties of the obtained coating were tested: the Vickers hardness was 634 Hv 0.2 , the bonding strength is 67 MPa.

[0044] The parameters for the tribological properties test were the same as those in Example 1. The friction coefficient and wear rate of the NiCrAlY / 10Al2O3 / 20h-BN composite coating obtained by the test are shown in Table 2. The friction coefficient at 900°C is 0.47, and the wear rate from room temperature to 600°C is 10 - 5 mm 3 / N·m, and the wear rate at 900 ℃ is as low as 5.3×10 -6 mm 3 / N·m.

[0045] Table 2 Tribological performance test results Example 3 A method for preparing a high-temperature wear-resistant nickel-based metal-ceramic composite coating comprises the following steps: ⑴Preparation of spray powder: 105 g of NiCrAlY powder, 30 g of Al2O3 ceramic powder, and 15 g of Ag-Mo mixed powder (Ag:Mo=2:1), (NiCrAlY, Al2O3 and Ag-Mo account for 70%, 20% and 10% by mass respectively) were mechanically mixed in a planetary ball mill, with steel balls, a ball-to-material ratio of 1:1, a rotation speed of 300 r / min, and a mixing time of 5 h. After uniform mixing, NiCrAlY / 20Al2O3 / 10Ag-Mo mixed powder was obtained.

[0046] ⑵Substrate pretreatment: The 304 stainless steel substrate was sandblasted with corundum sand of 100-200 μm particle size, with a sandblasting pressure of 0.5-0.6 MPa, a sandblasting angle of 40-50°, and a sandblasting distance of 80-90 mm. The stainless steel substrate was ultrasonically cleaned in anhydrous ethanol for 0.5 h before and after sandblasting. Finally, it was blown dry to obtain the pretreated substrate.

[0047] ⑶Preparation of coating: First, a NiCrAlY bonding layer with a thickness of about 40 μm was deposited on the surface of the pretreated substrate by explosion spraying technology, with an oxygen-fuel ratio of 1.1:1, an aeration volume of 45%-50%, a spraying frequency of 3 Hz, and a spraying distance of 150 mm. Then, NiCrAlY / 20Al2O3 / 10Ag-Mo mixed powder was deposited on the NiCrAlY bonding layer by explosion spraying technology, with an oxygen-fuel ratio of 1.3:1, an aeration volume of 45%-50%, a spraying frequency of 4 Hz, and a spraying distance of 250 mm. After cooling to room temperature, the NiCrAlY / 20Al2O3 / 10Ag-Mo composite coating was obtained.

[0048] The mechanical properties of the obtained coating were tested: Vickers hardness was 657 Hv 0.2 , the bonding strength is 68 MPa.

[0049] The tribological properties test method is the same as that in Example 1. The friction coefficient and wear rate of the NiCrAlY / 20Al2O3 / 10Ag-Mo composite coating obtained by the test are shown in Table 3. The friction coefficient is as low as 0.42 at 600°C. The wear rate increases first and then decreases with the increase of temperature. It decreases to 6.4×10 -6 mm 3 / N·m.

[0050] Table 3 Tribological performance test results Example 4 A method for preparing a high-temperature wear-resistant nickel-based metal-ceramic composite coating comprises the following steps: ⑴Preparation of spray powder: 105 g of NiCrAlY powder, 22.5 g of Al2O3 ceramic powder, and 22.5 g of Ag-Mo mixed powder (Ag:Mo=2:1; NiCrAlY, Al2O3 and Ag-Mo account for 70%, 15% and 15% by mass respectively) were mechanically mixed in a planetary ball mill, with steel balls, a ball-to-material ratio of 1:1, a rotation speed of 250 r / min, and a mixing time of 8 h. After uniform mixing, NiCrAlY / 15Al2O3 / 15Ag-Mo mixed powder was obtained.

[0051] ⑵Substrate pretreatment: The 304 stainless steel substrate was sandblasted with corundum sand of 100-200 μm particle size, with a sandblasting pressure of 0.6-0.7 MPa, a sandblasting angle of 50-60°, and a sandblasting distance of 90-100 mm. The stainless steel substrate was ultrasonically cleaned in anhydrous ethanol for 0.5 h before and after sandblasting. Finally, it was blown dry to obtain the pretreated substrate.

[0052] ⑶Preparation of coating: First, a NiCrAlY bonding layer with a thickness of about 40 μm was deposited on the surface of the pretreated substrate by explosion spraying technology, with an oxygen-fuel ratio of 1.1:1, an aeration volume of 45%~50%, a spraying frequency of 3 Hz, and a spraying distance of 150 mm. Then, NiCrAlY / 15Al2O3 / 15Ag-Mo mixed powder was deposited on the NiCrAlY bonding layer by explosion spraying technology, with an oxygen-fuel ratio of 1.2:1, an aeration volume of 45%~50%, a spraying frequency of 5 Hz, and a spraying distance of 200 mm. After cooling to room temperature, the NiCrAlY / 15Al2O3 / 15Ag-Mo composite coating was obtained.

[0053] The mechanical properties of the obtained coating were tested: the Vickers hardness was 618 Hv 0.2 , the bonding strength is 65 MPa.

[0054] The parameters for the tribological performance test were the same as those in Example 1. The friction coefficient and wear rate of the NiCrAlY / 15Al2O3 / 15Ag-Mo composite coating obtained by the test are shown in Table 4. The friction coefficient was as low as 0.36 at 600°C, and the wear rate increased first and then decreased with the increase of temperature, and decreased to 1.20×10 -5 mm 3 / N·m.

[0055] Table 4 Tribological performance test results Example 5 A method for preparing a high-temperature wear-resistant nickel-based metal-ceramic composite coating comprises the following steps: ⑴Preparation of spray powder: 105 g of NiCrAlY powder, 15 g of Al2O3 ceramic powder, and 30 g of Ag-Mo mixed powder (Ag:Mo=2:1), (NiCrAlY, Al2O3 and Ag-Mo account for 70%, 10% and 20% by mass respectively) were mechanically mixed in a planetary ball mill, with steel balls, a ball-to-material ratio of 1:2, a rotation speed of 300 r / min, and a mixing time of 6 h. After uniform mixing, NiCrAlY / 10Al2O3 / 20Ag-Mo mixed powder was obtained.

[0056] ⑵Substrate pretreatment: The 304 stainless steel substrate was sandblasted with corundum sand of 100-200 μm particle size, with a sandblasting pressure of 0.7-0.8 MPa, a sandblasting angle of 70-80°, and a sandblasting distance of 90-100 mm. The stainless steel substrate was ultrasonically cleaned in anhydrous ethanol for 0.5 h before and after sandblasting. Finally, it was dried to obtain the pretreated substrate.

[0057] ⑶Preparation of coating: First, a NiCrAlY bonding layer with a thickness of about 40 μm was deposited on the surface of the pretreated substrate by explosion spraying technology, with an oxygen-fuel ratio of 1.1:1, an aeration volume of 45%-50%, a spraying frequency of 3 Hz, and a spraying distance of 150 mm. Then, NiCrAlY / 10Al2O3 / 20Ag-Mo mixed powder was deposited on the NiCrAlY bonding layer by explosion spraying technology, with an oxygen-fuel ratio of 1.2:1, an aeration volume of 45%-50%, a spraying frequency of 5 Hz, and a spraying distance of 200 mm. After cooling to room temperature, the NiCrAlY / 10Al2O3 / 20Ag-Mo composite coating was obtained.

[0058] The mechanical properties of the obtained coating were tested: Vickers hardness was 582 Hv 0.2 , the bonding strength is 60 MPa.

[0059] The parameters for the tribological performance test were the same as those in Example 1. The friction coefficient and wear rate of the NiCrAlY / 10Al2O3 / 20Ag-Mo composite coating obtained by the test are shown in Table 5. The friction coefficient was as low as 0.34 at 600°C, and the wear rate first increased and then decreased with the increase of temperature. The wear rate at 900°C was 2.17×10 -5 mm 3 / N·m.

[0060] Table 5 Tribological performance test results .

Claims

1. A high temperature wear-resistant nickel-based metal-ceramic composite coating, characterized in that: The coating is composed of 70% NiCrAlY powder as a matrix, 10-20% Al2O3 ceramic powder as a wear-resistant phase and 10-20% lubricating phase by mass percentage; the lubricating phase is composed of one or two of h-BN, Ag powder and Mo powder; the h-BN refers to a nickel-coated core-shell structure powder in which 60% by mass of metal Ni is used as a shell layer around a 40% h-BN core.

2. A high temperature wear-resistant nickel-based metal-ceramic composite coating as claimed in claim 1, characterized in that: When the lubricating phase is h-BN, the mass fraction of h-BN is 10% or 20%.

3. A high temperature wear-resistant nickel-based metal-ceramic composite coating as claimed in claim 1, characterized in that: When the lubricating phase consists of Ag powder and Mo powder, the mass ratio of the Ag powder to the Mo powder is 2:

1.

4. A high temperature wear-resistant nickel-based metal-ceramic composite coating as claimed in claim 1, characterized in that: The particle size of the NiCrAlY powder is 15-45 μm; the particle size of the Al2O3 ceramic powder is 15-40 μm; the particle size of the h-BN is 5-100 μm; the particle size of the Ag powder is 15-55 μm; and the particle size of the Mo powder is 20-55 μm.

5. The high temperature wear-resistant nickel-based metal-ceramic composite coating according to claim 1, characterized in that: The Vickers hardness of the coating is 582~678 Hv 0.2 The bonding strength is greater than 60 MPa, and the wear rate at 900 °C is reduced to 10 -6 mm 3 / N·m.

6. The method for preparing a high temperature wear-resistant nickel-based metal-ceramic composite coating according to claim 1, comprising the following steps: ⑴Preparation of spray powder: Weigh NiCrAlY powder, Al2O3 ceramic powder and lubricating phase powder according to a proportion, and mix the NiCrAlY powder, Al2O3 ceramic powder and lubricating phase powder uniformly by mechanical mixing to obtain spraying powder; ⑵Substrate pretreatment: The surface of the 304 stainless steel substrate was first ultrasonically cleaned with anhydrous ethanol for 0.5 h, then sandblasted, then ultrasonically cleaned with anhydrous ethanol for 0.5 h, and finally dried to obtain a pretreated substrate. ⑶Preparation of coating: First, a NiCrAlY bonding layer with a thickness of 30-50 μm is deposited on the surface of the pretreated substrate by using the explosion spraying technology, and then the spraying powder is deposited on the NiCrAlY bonding layer by using the explosion spraying technology. After cooling to room temperature, a high-temperature wear-resistant nickel-based metal-ceramic composite coating is obtained.

7. The method for preparing a high temperature wear-resistant nickel-based metal-ceramic composite coating according to claim 6, characterized in that: The mechanical mixing conditions in step (1) are as follows: a planetary ball mill is used, the grinding balls are steel balls, the ball-to-material ratio is 1:1-1:2, the rotation speed is 250-300 r / min, and the mixing time is 5-8 h.

8. The method for preparing a high temperature wear-resistant nickel-based metal-ceramic composite coating according to claim 6, characterized in that: The sandblasting conditions in step (2) refer to using corundum sand with a particle size of 100-200 μm, a sandblasting pressure of 0.5-0.8 MPa, a sandblasting angle of 40-90°, and a sandblasting distance of 50-100 mm.

9. The method for preparing a high temperature wear-resistant nickel-based metal-ceramic composite coating according to claim 6, characterized in that: The conditions for explosion spraying in step (3) refer to using a mixed gas of oxygen and fuel gas with an oxygen-fuel ratio of 1.1:1~1.3:1, the fuel gas is a mixture of acetylene and propane, the inflation volume is 45%~50%, the spraying frequency is 3~5 Hz, the spraying distance is 150~200 mm, and nitrogen is used as the powder delivery carrier gas and protective gas.

Citation Information

Patent Citations

  • A nickel-based alumina high-temperature self-lubricating wear-resistant coating and its preparation method

    CN109868443B

  • A method for preparing a nickel-based lubricating coating by explosion spraying

    CN115537704B

  • Explosion spraying nickel-based wide-temperature-range self-lubricating coating

    CN116445846A

  • Preparation technology for all-metal-phase wide-temperature-range self-lubricating coating

    CN104278227A

  • Titanium alloy blade mid-span shroud wear-resistant coating repairing method

    CN112410712A

Cited By

  • Anti-adhesion asphalt drying device

    CN120593478A

  • High-wear-resistance silicon nitride-based ultrahigh-temperature self-lubricating composite material and preparation method thereof

    CN121109841A